Electrochemical degradation of reactive orange 16 by using charcoal-based metallic composite electrodes - Zuhailie Zakaria; Mohamed Rozali Othman; Siti Zubaidah Hasan; Wan Yaacob Wan Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2019)
The performance of charcoal composite electrodes, by using commercial activated charcoal and charcoals from coconut trunk, mangrove wood, rubber wood, and sugarcane, was compared in an attempt to fabricate effective and low cost electrodes for wastewater treatment in textile industries. Reactive Orange 16 was chosen as a model dye because of its high resistance towards conventional treatment methods, while sodium chloride was selected as a supporting electrolyte. The electrode efficiencies were determined based on the percentage of Reactive Orange 16 decolourisation. The charcoals used, duration of electrolysis, functional groups present in charcoals, Brunauer-Emmett-Teller surface area and production of hypochlorite ion that contribute to the effectiveness of the electrodes were examined. The coconut trunk, rubber wood, sugarcane, mangrove wood, and commercially available activated charcoals that were incorporated into tin composite electrodes were able to degrade Reactive Orange 16 until 98.5%, 96.2%, 83.0%, 71.2%, and 29.6%, respectively, after 20 min of electrolysis. The degradation increases with duration of electrolysis. This study illustrated that the production of hypochlorite ion from sodium chloride in solution was the main factor that enhanced the Reactive Orange 16 colour removal. Adsorption process on the electrode surface did not play any significant role in the dye decolourisation.